Optogenetic measurement of presynaptic calcium transients using conditional genetically encoded calcium indicator expression in dopaminergic neurons. - Carmelo Sgobio; David A Kupferschmidt; Guohong Cui; Lixin Sun; Zheng Li; Huaibin Cai; David M Lovinger (PLoS ONE)
Calcium triggers dopamine release from presynaptic terminals of midbrain dopaminergic (mDA) neurons in the striatum. However, calcium transients within mDA axons and axon terminals are difficult to study and little is known about how they are regulated. Here we use a newly-developed method to measure presynaptic calcium transients (PreCaTs) in axons and terminals of mDA neurons with a genetically encoded calcium indicator (GECI) GCaMP3 expressed in transgenic mice. Using a photomultiplier tube-based system, we measured electrical stimulation-induced PreCaTs of mDA neurons in dorsolateral striatum slices from these mice. Single-pulse stimulation produced a transient increase in fluorescence that was completely blocked by a combination of N- and P/Q-type calcium channel blockers. DA and cholinergic, but not serotoninergic, signaling pathways modulated the PreCaTs in mDA fibers. These findings reveal heretofore unexplored dynamic modulation of presynaptic calcium in nigrostriatal terminals.